THE IDENTIFICATION OF SENIOR LIVING DESIGN WITH THE APPROACH OF BEHAVIORAL AND ENVIRONMENTAL ARCHITECTURE - Yaseri Dahlia Apritasari; Shelly Antoni (Department of Architecture Universitas Muhammadiyah Jakarta, 2023)
Currently, Indonesia is experiencing the phenomenon of an Aging Population, along with the increasing elderly population. Then facilities are needed for the elderly in the form of nursing homes. However, existing nursing homes have limited facilities and activities for the elderly. One of the strategies for fulfillment above is the Senior Living facility, as a residence that focuses on the elderly community who are productive and active in social and economic aspects, as well as living prosperously and happily. To increase the productivity of the elderly, senior living design strategies can use environmental and behavioral architecture approaches. This study aims to determine the indicators of senior living design with an environmental, architectural, and behavioral approach. This research method uses descriptive qualitative with stages: (1) Observation of behavior and facilities in three Senior Living case studies. (2) Identify indicators of environmental architecture design and behavior in three Senior Living case studies. (3) Senior Living design recommendations with an environmental and behavioral architecture approach. The results showed the form of application related to the criteria that need to be considered in designing Senior Living.